Optimization of the thermodynamic configurations of a thermoacoustic engine auxiliary power unit for range extended hybrid electric vehicles. (15th March 2020) - Nader, Wissam Bou; Chamoun, Joy; Dumand, Clément
Abstract: Significant research efforts are considered in the automotive industry on the use of low carbon alternative fuels in order to reduce carbon emissions of future vehicles, some of which are only compatible with external combustion machines. These machines are only suitable for electrified powertrains relying on electric propulsion, particularly in range extenders, where the energy converter operates steadily at a constant power at its optimal efficiency. The fuel consumption of these powertrains strongly relies on the performance of the energy converter in terms of efficiency, as well as on the deployed energy management strategy. This paper investigates the potential of fuel savings of a Extended Range hybrid Electric Vehicle (EREV) using a Thermoacoustic Engine (TAE) system as energy converter substitute to the conventional Internal Combustion Engine (ICE). An exergo-technological explicit analysis is conducted to identify the different TAE-system thermodynamic configurations. The Regenerative Reheat two-stage thermoacoustic engine is selected among numerous identified thermodynamic configurations, offering high efficiency and net specific work compared to other configurations. An EREV model is developed and the presented RRe-n2-TAE configuration is integrated. Fuel consumption simulations are performed on the Worldwide-harmonized Light Vehicles Test Cycle (WLTC). Results are compared to the reference ICE-APU. Results show more than 20% of fuel savings with the RRe-n2-TAE as Auxiliary Power Unit (APU) compared to the basic TAE configuration and comparable fuel consumption with the ICE. Consequently, the studied RRe-n2-TEG-APU presents a potential for the implementation in EREVs with zero carbon alternative fuels. Highlights: Study assesses Thermoacoustic external combustion system for hybrid vehicles. Exergo-technological explicit analysis is used to find the best system configuration. Regenerative reheat two-stages thermoacoustic engine is prioritized. Fuel savings compared to internal combustion engine are observed with the prioritized configuration.